If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = 2x + -2 + x + 5 Reorder the terms: 90 = -2 + 5 + 2x + x Combine like terms: -2 + 5 = 3 90 = 3 + 2x + x Combine like terms: 2x + x = 3x 90 = 3 + 3x Solving 90 = 3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 90 + -3x = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 90 + -3x = 3 + 0 90 + -3x = 3 Add '-90' to each side of the equation. 90 + -90 + -3x = 3 + -90 Combine like terms: 90 + -90 = 0 0 + -3x = 3 + -90 -3x = 3 + -90 Combine like terms: 3 + -90 = -87 -3x = -87 Divide each side by '-3'. x = 29 Simplifying x = 29
| 1/6x-4 | | 7/2d-2/d=3/4-1/4d | | (9+4d)=15 | | 12(2k+11)=+12(2k+12) | | 22=64+m | | 2n+16=5n-5 | | -19x+5y=-17 | | K*-3-11=-20 | | -8=3(x-2) | | 550=8x | | 2(9x+9)-10x=8x+6-10 | | 7-6X=1.2-2X | | B-9/10b+6=11 | | 5/2-1 | | 5x-2x=51 | | 6h-15+12h+8=11 | | 5x-2+3x^2=0 | | 8(w+6)=7w-2 | | 350+x=3650 | | 2/3r+4=12 | | (-7i)+(2i)-(-2-4i)= | | -3(7x-5)+8=-21x+23 | | f(x)=-4+8 | | 12(2+2z)=-4z-4(-12z-1) | | (32.50x+3.30)+5.90x=220.70 | | 3y+39=16y | | 8(w+9)=7w-2 | | 3/7x+4 | | (32.50x+3.30)+5.90=220.70 | | -9/4-1/5u=-8/3 | | T=gr+g*vtforg | | 2/3x+8=-2 |